Progressive multifocal leukoencephalopathy limited to the posterior fossa - Rahmat, K.; Kaur, S.; Ramli, N.M.; Chandran, P.A.; Wong, Kum Thong; Abdullah, S.; Omar, S.S.; Ganesan, D.; Tan, Chong Tin (2010)
Progressive multifocal leukoencephalopathy (PML) is a rapidly progressive demyelinating disease caused by the reactivation of JC papova virus usually in immunocompromised hosts.(1) The disease is a chronic viral infection resulting in mortality within a year.(2) The condition characterized by white matter changes in multiple locations of the brain is caused by destruction of the oligodendrogliocytes.(2) We report a case of AIDS associated PML presenting with progressive cerebellar symptoms, with the unusual feature of imaging abnormalities limited to the posterior fossa.